1973
DOI: 10.1172/jci107274
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Sodium Loading and Sodium Restriction on Plasma Prostaglandin A, E and F Concentrations in Normal Humans

Abstract: A B S T R A C T It has been suggested that prostaglandins may be involved in the control of sodium homeostasis. Prostaglandin A and prostaglandin E have been shown to increase renal blood flow and urinary sodium excretion and prostaglandin A has been shown to stimulate aldosterone release. The purpose of this study was to determine the effect of chronic sodium loading and sodium restriction on plasma prostaglandin A, E, and F concentrations.Seven normal human volunteers were placed on three sodium intake diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(16 citation statements)
references
References 22 publications
2
13
0
1
Order By: Relevance
“…Terragno et al [20] found an increased PG biosynthesis in kidneys chronically exposed to an excess of Na+; and other authors have reported a reduction of endogenous PG lev el after salt-loading [22,25,26]. Consider ing all these data, our results suggest that after salt-loading, there was no close corre lation between RIC granularity and PG lev el or PG biosynthesis in the kidneys.…”
Section: Discussionsupporting
confidence: 46%
“…Terragno et al [20] found an increased PG biosynthesis in kidneys chronically exposed to an excess of Na+; and other authors have reported a reduction of endogenous PG lev el after salt-loading [22,25,26]. Consider ing all these data, our results suggest that after salt-loading, there was no close corre lation between RIC granularity and PG lev el or PG biosynthesis in the kidneys.…”
Section: Discussionsupporting
confidence: 46%
“…The plasma concentration of endogenous PGE1 at steady state is approximately 0.25 ng/mL. 35 Analysis of fundus photographs showed that PGE1 substantially dilated the retinal vessels. Typically 10 to 20 minutes after the start of PGE1 administration, some patients reported brightening of their vision.…”
Section: Discussionmentioning
confidence: 99%
“…In human lung, for example, the PGE 2 concentration is about 25 ng/gram tissue, or ‫ف‬ 70 nM; in human semen this value is ‫ف‬ 25 g/ml, or ‫ف‬ 70 M (53). On the other hand, plasma PGE and PGF concentrations in humans are ‫ف‬ 0.25 ng/ml, or 0.7 nM (54). Assuming that hPGT is the mechanism for reuptake of PGs after their release, this plasma concentration would represent the residual from such a process.…”
Section: Discussionmentioning
confidence: 99%